A Novel Approach to Minimize Energy Requirements and Maximize Biomass Utilization of the Sugarcane Harvesting System in Sri Lanka - Thilanka Ariyawansha; Dimuthu Abeyrathna; Buddhika Kulasekara; Devananda Pottawela; Dinesh Kodithuwakku; Sandya Ariyawansha; Natasha Sewwandi; WBMAC Bandara; Tofael Ahamed; Ryozo Noguchi (Energies, 2020)
Sugarcane harvesting requires a significant amount of energy and time to manage dry leaves after the harvesting process. Therefore, the objective of this study was to minimize the energy requirement to process the cane and dry leaves’ harvesting (CDLH) for sugarcane while, at the same time, maximizing sugar production from cane and energy from dry leaves in Sri Lanka. The CDLH was conceptualized using a novel approach to optimize sugarcane harvesting to maximize biomass supply for energy production while reducing supply chain sugar-loss. The CDLH was investigated for manual harvesting capacity, energy consumption, sugar loss, and biomass energy potential. It was observed that CDLH consumed higher energy compared to the present practices of harvesting. However, the energy used for fieldwork was reduced because of the shifting of cane chopping and cleaning from the field to the factory. Low bulk density of the harvested cane of the CDLH system had a higher energy requirement in transportation. Comparatively, CDLH showed higher biomass energy potential and less sugar loss. High energy potential increases the energy potential to consumption ratio compared to the existing method. Therefore, the theoretical evaluation showed that the CDLH system can produce more than 20 kg of sugar and 879 MJ of electricity when processing 1 t of sugarcane.